2016
DOI: 10.21837/pm.v14i5.186
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing Urban Spatial Growth for the George Town Conurbation

Abstract: Urban growth, which caused spatial land use and land cover changes has affected various physical environment, social, and economic activities. Thus, in order to understand the dynamic process of urban spatial growth, researchers throughout the world have implemented diverse approaches, where spatial models have been developed to predict and simulate future urban growth. Those models were developed based on the driving forces that stimulate urban spatial growth. Therefore, in ensuring reliable models to be deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Peri-urban area is indeed the area where massive LUCC tend to occur to support the urban area. Finding from Mahamud et al (2016) shows that the distance between public facilities, housing price and distance between workplace are the factors driving urban area development. This happens because urban areas with limited space couldn’t provide the criteria as mentioned previously; therefore, the development will be expanding vertically and horizontally and keep expanding into the nearby area (Su et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Peri-urban area is indeed the area where massive LUCC tend to occur to support the urban area. Finding from Mahamud et al (2016) shows that the distance between public facilities, housing price and distance between workplace are the factors driving urban area development. This happens because urban areas with limited space couldn’t provide the criteria as mentioned previously; therefore, the development will be expanding vertically and horizontally and keep expanding into the nearby area (Su et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…By the same token, the establishment of an IHL in an area can spark development in three aspects; economy, society, and environment [6]. On the other hand, Mahamud et al [22] identified three major elements that promote urban development: physical, socioeconomic, and environmental factors. Distance to the workplace, low-cost housing, and distance to public facilities, to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In what seems not to be clear in the literature is the arguments on the factors that can positively influence UAG. While Mahamud, Samat, and Noor (2016) attribute that the factors that affect urbanization equally influence UAG which includes but not limited to employment opportunities, social factors, increase in income in urban centres, industrialization, education spread, modernization, and infrastructural developments. These factors can equally be companied with other negative factors such as an increase in crimes, growing of slums as well as frustration among the rural–urban migrants and economically displaced individual within the urban areas (Mahamud et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While Mahamud, Samat, and Noor (2016) attribute that the factors that affect urbanization equally influence UAG which includes but not limited to employment opportunities, social factors, increase in income in urban centres, industrialization, education spread, modernization, and infrastructural developments. These factors can equally be companied with other negative factors such as an increase in crimes, growing of slums as well as frustration among the rural–urban migrants and economically displaced individual within the urban areas (Mahamud et al, 2016). In SSA, an increase in the gross domestic product (GDP), total trade (TRD), and foreign direct investment (FDI) have contributed in different ways to economic growth and development.…”
Section: Introductionmentioning
confidence: 99%